2018
DOI: 10.1002/rcr2.317
|View full text |Cite
|
Sign up to set email alerts
|

Central airway obstruction caused by adenoid cystic carcinoma in pregnancy: a case report and review of the literature

Abstract: Malignancy complicates one in a thousand pregnancies. The most frequently diagnosed of these are breast, cervical, melanoma, ovarian, and haematological neoplasms. Tumours of respiratory origin are very uncommon during pregnancy. We present a case of tracheal adenoid cystic carcinoma (ACC), a rare type of primary airway tumour, diagnosed in a pregnant woman. To our knowledge, this is the third reported case of tracheal ACC complicating pregnancy. We discuss potential barriers to timely diagnosis of malignancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Primary bronchial tumors are extremely rare [ 1 , 2 ]. As the disease progresses, the tumor obstructs the airway, resulting in symptoms such as coughing, wheezing, pneumonia, and dyspnea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary bronchial tumors are extremely rare [ 1 , 2 ]. As the disease progresses, the tumor obstructs the airway, resulting in symptoms such as coughing, wheezing, pneumonia, and dyspnea.…”
Section: Introductionmentioning
confidence: 99%
“…As the disease progresses, the tumor obstructs the airway, resulting in symptoms such as coughing, wheezing, pneumonia, and dyspnea. Since these symptoms are not specific to this disease, primary bronchial tumors are often misdiagnosed as bronchial asthma or chronic obstructive pulmonary disease [ 2 ]. This case report describes a bronchial tumor which mimicked deteriorating bronchial asthma in a pregnant patient.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have not found an association between smoking status and ACC or a gender predilection for this tumor. In contrast, our study included disproportionately more non-smoking male patients 1,2 .…”
Section: Discussionmentioning
confidence: 98%
“…Malignant airway obstruction should be considered in patients with obstructive airway disease not responding to bronchodilators and inhaled steroids. When patients with ACC develop new symptoms during follow-up, the possibility of disease recurrence should be considered before attributing the symptoms to comorbidities or side effects of oncologic treatment 1,2,7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation